Integrating ligand and structure-based discovery approaches to unravel potential novel glyoxalase-I inhibitors - Roa’a Bani-Khalaf, Qosay Al-Balas, Soraya Alnabulsi (Journal of Applied Pharmaceutical Science, 2024)
The early 1900s discovery of the glyoxalase system revealed its numerous biological functions, including cancer. The conversion of harmful ketoaldehydes like methylglyoxal into nontoxic metabolites by this mechanism is crucial. Cells maintain their physiological functions through this procedure. Blocking this pathway in cancer cells causes hazardous chemicals to accumulate, triggering apoptosis. The molecular modeling component of this study has employed the following techniques: ligand-based drug design, structure-based drug design, ligand-pharmacophore mapping for zinc binding groups, and docking using the CDOCKER protocol. The initial step involved gathering the structures of glo-inhibitors from existing literature. These structures were then divided into two sets: a “training set” used to construct the pharmacophores, and a “test set” used to validate the created pharmacophores. Subsequently, the validated pharmacophores were employed to conduct a search in the ASINEX® commercial chemical repository, with the aim of identifying molecules that conform to these pharmacophores. The retrieved compounds underwent a thorough screening process to determine their priority as potent inhibitors. This stage has employed molecular docking and “calculate total binding energy (TBE)” to select the best candidates for the purchasing process. After buying the compounds, their glo-I inhibition and IC50 values were tested in vitro. Overall, 15 promising compounds were found. Four of the 15 compounds exhibited in vitro activity. The most active molecule, BAS00323528, having a thiazolidinedione scaffold, had an IC50 value of 2.79 μM.
Keywords: Glyoxalase-I, common feature pharmacophore, docking, ROC analysis, Zinc Binding Group